HTTPS://DOI.ORG/10.36873/JHT.V14I1.327: WILLINGNESS TO PAY FOR MANGROVES CONSERVATION BY THE LOCAL COMMUNITIES IN SALUT MENGKABONG LAGOON, TUARAN SABAH, ANDY R. MOJIOL1), KUAN YEN HONG2) & EJRIA SALEH2) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThis research aimed to investigate the Willingness to Pay (WTP) for mangroveconservation of local communities at Salut Mengkabong Lagoon, Tuaran based on theamount of fees imposed on them. The content is based on questionnaire survey providedto local communities from Mangrove Forest Produce (MFP) to their perception inconservation programme. The survey was conducted with a priod of 7 month startedfrom September 2016 until March 2017. Contingent Valuation Method (CVM) was usedto calculate the Willingness to Pay (WTP) whereby 100 respondents were asked tocomplete the questionnaire. From the analysis, it showed that the WTP of localcommunities were affected by their monthly income. Regression model analysis withWTP = -0.087* (monthly income) + 1.789 has been formed. Whereas, the value ofmangrove forest produce (MFP) in Salut Mengkabong Lagoon has been calculated with atotal of RM728 for the direct product while for the non-direct products such as crab,bivalves, seashells and fishes cost about RM721 to RM2472 in a year. The studydocumented mangrove forest contribution to local communities in Salut MengkabongLagoon such as timber; Rhizophora mucronata and Avicennia spp, Seafood; Scyllaserrata, Geloina coaxans, various type of fishes and seashell. From the result, it washope that this study can promote a win-win situation to both local community andstakeholders to come out with an effective supervision to ensure the long-lastingdependency of local communities to the mangrove forests without undermining theirsocio-economic wellbeing.Keywords: Salut Mengkabong Lagoon, Mangroves Forest Produce, local community